The Important Role Of Internal Control In Accounting Information Systems - Salomi Jacomina Hehanussa (Asian Journal of Social and Humanities, 2024)
This study discusses the important role of internal control in Accounting Information Systems. The purpose of this writing is to provide an overview or explanation with a literature study approach on the important role of internal control in accounting information systems. In addition, the writing of this paper aims to provide knowledge of whether the use of computer-based accounting information systems can guarantee the success of a company without supervision from the company's business people. The author discovers six important roles of the Internal Control System. The first is to have a great influence on computer-based Accounting Information Systems. Internal Control Systems can prevent excessive resources in the company, Create accountability of financial statements, and increase the credibility and quality of the company; then, its management makes it easy to make decisions and prevent fraud. Accountant information computer-based systems cannot run properly without management control.